2019
DOI: 10.1007/s00213-019-05331-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of modulation of the α7 nicotinic acetylcholine receptor on nicotine reward in the mouse conditioned place preference test

Abstract: Rationale The α7 nicotinic acetylcholine receptor (nAChR) has been implicated as a target in modulating nicotine reward. However, the effect of pharmacological agents that have been shown to alter the channel properties of the α7 nAChR is not well understood in nicotine reward. Objectives This study aimed to investigate the impact of α7 nAChR pharmacological modulation on nicotine conditioned place preference (CPP) in mice by using positive allosteric modulators (PAMs) and a silent agonist. Methods The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We also assessed whether KP (30 mg/kg; i.p.) can trigger brain reward mechanisms by measuring conditioned place preference (CPP) 46,47 , and observed no such effects (Supplementary Fig. 3d).…”
Section: Resultsmentioning
confidence: 97%
“…We also assessed whether KP (30 mg/kg; i.p.) can trigger brain reward mechanisms by measuring conditioned place preference (CPP) 46,47 , and observed no such effects (Supplementary Fig. 3d).…”
Section: Resultsmentioning
confidence: 97%
“…Enhancing KYNA levels in the brain prevents nicotine-induced increases in dopamine (Erhardt et al, 2001 ) and glutamate (Konradsson-Geuken et al, 2009 ), reduces the reinforcing properties of Tetrahydrocannabinol (THC) (Justinova et al, 2013 ), and reduces nicotine craving and relapse (Secci et al, 2017 ). Although α7 PAMs have been reported to reduce the reinforcing properties of nicotine (Jackson et al, 2019 ), complete dose-response analyses have indicated that α7 PAMs produce leftward-shifts (increase sensitivity) in the dose-response curve for nicotine reward behaviors (Perkins et al, 2018 ). Recent clinical data have indicated that treatment with an α7 PAM increased nicotine craving and nicotine use (Perkins et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also tested whether KP (30 mg/kg; i.p.) can trigger brain reward mechanisms by assessing conditioned place preference (Jackson et al, 2019;Sora et al, 1998), and there were no such effects ( Fig. 2E).…”
Section: Compound Screen In Primary Cortical Neurons For Kcc2 Gene Exmentioning
confidence: 94%